Effect ofÂ theÂ composting process onÂ physicochemical properties andÂ concentration ofÂ heavy metals inÂ market waste withÂ additive materials inÂ theÂ Ga West Municipality, Ghana - Carl Tibu; Ted Y. Annang; Negasi Solomon; Dzidzo Yirenya-Tawiah (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The main objective of this study was to assess the physiochemical properties and phytotoxicity of compost made from different organic waste materials sourced from local markets. Methods The Stack pile composting was carried out with market waste, sawdust, rice straw, and swine manure in four different combinations. Parameters such as temperature, pH, nitrogen, phosphorus, potassium, and heavy metal concentrations were monitored. Germination test with water extracts of the composts was done to assess phytotoxicity of the composts. Results All compost piles recorded temperatures of 38 °C slightly above the recorded ambient temperature of 34 °C at the start of composting. The pH value ranged from 7.12 to 8.2 for the different compost types. The total organic carbon and total nitrogen values ranged from 27.05â31.06 to 0.77â0.97%, respectively. The total phosphorus and total potassium values ranged from 0.2â1.87 to 0.39â2.3%, respectively, for different compost types. The C/N ratio values ranged from 29.09:1 to 36.22:1. All the composts had heavy metal concentrations below the Canadian Council of Ministers of the Environment standards. Germination indices, a measure of plant vs supporting potential, ranged from 80 to 99% for Solanum lycopersicum, 170 to 198% for Cucumis sativus, and 114 to 166% for Brassica oleracea. Conclusion The study confirms the notion that composting municipal solid waste is a viable organic waste management strategy, and with the potential to enhance waste management system, while promoting cultivation of vegetables for food security.